L’effet de l’anastomose ou de la splénectomie artificielle de la cavité porte sur l’hémodynamisme hépatique et porte en cirrhotique - Bláha, V.; Vosmík, J. (Nuklearmedizin - NuclearMedicine, 1969)
Using their own modified method the authors simultaneously examined the blood clearances of 198Au colloid and 131I-Rose Bengal and determined the ratio1. in a group of 11 patients with severe liver cirrhosis, portal hypertension and portosystemic shunts, both before and after artificial portocaval anastomosis, and2. in two patients with thrombosis v. lienalis, excessive splenomegaly and extensive portosystemic shunts before and after splenectomy. Ad 1. In 6 patients 55%) a reduction of the effective liver blood flow occured due to the artificial portosystemic anastomosis; the average decrease was ~ 20%. In 7 patients a significant enlargement of the total splenosystemic flow was observed as a result of the artificial communication.Ad 2. In both patients an increase of the effective liver blood flow occured after splenectomy. The minimal preoperative splenosystemic flow was ~ 0.152 and ~ 0.089 of the circulating blood per minute (expressed by means of kAu).The authors discuss the significance of the kAu and kBR values as well as that of the ratio for the estimation of changes in hepatic and portal haemodynamics.